Enhancing multi-skill development in 6-7-year-olds through the “Crocodile River,” “Socorro,” and “Meo Duoi Chuot” games in the kids’ athletics level 1 program - Kardi, Ipa Sari; Ansar CS; Ibrahim; Alimuddin; Nopiyanto, Yahya Eko (UIR Press, 2025)
Background: The decline in children’s physical activity in Papua poses a serious concern, particularly due to its negative impact on health and motor skill development. Limited multi-skill proficiency among young children contributes to reduced engagement in physical activities. Despite global efforts to promote physical literacy, few interventions have focused on culturally relevant and age-appropriate activities to improve multi-skills in early childhood, especially in underserved regions like Papua. Research Objectives: This study aimed to improve the multi-skill development of 6-7-year-old elementary school students through the implementation of the Kids’ Athletics Level 1 program, incorporating locally adapted games such as “Crocodile River,” “Socorro,” and “Meo Duoi Chuot.” Methods: A quasi-experimental design using a one-group pretest-posttest approach was employed. A total of 50 students aged 6-7 years were selected via purposive sampling. The Indonesian Physical Fitness Test was used to assess outcomes, including sit-and-reach, one-leg standing balance, tennis ball catch-and-throw, shuttle run, and an 800-meter run. Paired-sample t-tests were conducted to evaluate differences between pretest and posttest scores. Findings/Results: The analysis revealed a statistically significant improvement in students’ multi-skill performance (p < 0.05). The findings support the integration of the Kids' Athletics program into school curricula as an effective strategy to enhance motor competence in early childhood. Conclusion: The Kids’ Athletics Level 1 model, enriched with culturally adapted games, proves effective in developing fundamental multi-skills in young children. Physical Education teachers are encouraged to adopt this model alongside other programs to optimize physical development in early learners, particularly those in low-activity regions such as Papua.